1979
DOI: 10.1083/jcb.80.1.69
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of cell surface saccharides on pancreatic cells

Abstract: We describe here a simple, general procedure for the purification of a variety of lectins, and for the preparation of lectin4erritin conjugates of defined molar composition and binding properties to be used as probes for cell surface saccharides. The technique uses a "universal" affinity column for lectins and their conjugates, which consists of hog sulfated gastric mucin glycopeptides covalently coupled to agarose. The procedure involves: (a) purification of lectins by chromatography of aqueous extracts of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…It is not known whether morphogenesis and differentiation lead to a change in membrane properties, or if the change in membrane properties results in morphogenesis and differentiation. Studies of the pancreas showed that acinar cells strongly bind alliectins; on the other hand, endocrine and centroacinar cells selectively bind only certain specific lectins(60). The characteristics of these lectin receptors have been found to change during development of the…”
mentioning
confidence: 99%
“…It is not known whether morphogenesis and differentiation lead to a change in membrane properties, or if the change in membrane properties results in morphogenesis and differentiation. Studies of the pancreas showed that acinar cells strongly bind alliectins; on the other hand, endocrine and centroacinar cells selectively bind only certain specific lectins(60). The characteristics of these lectin receptors have been found to change during development of the…”
mentioning
confidence: 99%
“…To date, no direct cause and effect association has been reported, but alterations in membrane properties primarily lectin binding, have been documented in the pancreas (15,16) and small intestine (17).…”
Section: Biological Clockmentioning
confidence: 99%
“…In f ur t he r mo r e , th e c h a r n c t e r i s t 'i c s o f l e ctin b indin g h .i v o h l'L'Il lo u n d t o ,' h; lI1gL~d uri nu d cvo l opm cn t o f th e rat pnrr -.r c-n t i c-:]C iIl;lr (' vlls (10).…”
mentioning
confidence: 99%